Pengaruh Media Sosial, Keterampilan Dan Kreativitas Berwirausaha Terhadap Keberhasilan Usaha Pada UMKM Kopi Di Bondowoso - Duwi Antoro; Eko Budi Satoto; Wenny Murtaliningtyas (Universitas Muhammadiyah Metro, 2024)
Entrepreneurship is the effort to discover, develop, and combine innovations,opportunities, and better ways to enhance value in life. Entrepreneurial success occurswhen entrepreneurs experience improvement from previous outcomes and are part ofefforts involving all activities to demonstrate that they have achieved what they haveachieved. Numerous internal and external elements that influence the success and failureof businesses. The purpose of this study is to determine whether entrepreneurial skills,social media skills, and entrepreneurial creativity affect the success of coffee SMEs inBondowoso. Quantitative research was used. This study involved 67 respondents. UsingSPSS version 26, multiple linear regression analysis was performed. The coefficient ofdetermination test showed that entrepreneurial skills, social media skills, and creativityinfluence business success by 57.4%. The t-test results showed that entrepreneurial skills,social media skills, and entrepreneurial creativity have a significant influence on thesuccess of coffee SMEs in Bondowoso